Procalcitonin Outperforms NLR as a Sepsis Predictor in Pneumonia Patients: A Cross-Sectional Study from a Tertiary Hospital in Padang, Indonesia - Dina Fitri Fauziah; Aidillah Mayuda; Wici Septiyeni; Siska Armeinesya; Firmaweni; Atikah Dafri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Pneumonia remains a significant cause of morbidity and mortality worldwide, with sepsis being a severe complication. Early identification of sepsis is crucial for prompt treatment and improved outcomes. This study aimed to evaluate the performance of procalcitonin (PCT) and neutrophil-lymphocyte ratio (NLR) as predictors of sepsis in pneumonia patients at a tertiary hospital in Padang, Indonesia. Methods: A cross-sectional study was conducted on 110 adult pneumonia patients admitted to Dr. M. Djamil General Hospital Padang between 2022 and 2023. Data on demographics, clinical characteristics, NLR, and PCT levels were collected from electronic medical records. Sepsis was defined according to established clinical criteria. Receiver operating characteristic (ROC) curve analysis was performed to assess the diagnostic accuracy of NLR and PCT in predicting sepsis. Results: The study population had a mean age of 57.72 ± 14.41 years, with 56.4% being male. Of the 110 patients, 73.6% had community-acquired pneumonia (CAP) and 26.4% had hospital-acquired pneumonia (HAP). Sepsis was present in 55.5% of the patients. The median NLR and PCT levels were significantly higher in the sepsis group compared to the non-sepsis group (NLR: 14 vs. 6.6, p=0.002; PCT: 2.17 vs. 0.24, p=0.000). ROC analysis showed that PCT had a higher area under the curve (AUC) compared to NLR (0.724 vs. 0.676), indicating better diagnostic accuracy. The optimal cut-off point for PCT was 0.455, with a sensitivity of 65.6% and specificity of 65.3%. For NLR, the cut-off point was 10.375, with a sensitivity of 63.9% and specificity of 63.3%. Conclusion: PCT demonstrated superior diagnostic accuracy compared to NLR in predicting sepsis among pneumonia patients in this study. However, NLR remains a valuable tool, especially in resource-limited settings where PCT testing may not be readily available.